Dynamics of Administrative and Criminal Accountability in Cases of Abuse of Authority Resulting in State Losses According to Indonesian Law - Tubagus Rekayasa Kamal Djunaedi; Suparno Suparno (Riviera Publishing, 2025)
Abuse of authority by state officials in Indonesia remains a serious issue, not only violating regulations but also causing state financial losses and diminishing the quality of public services. This study examines the dynamics of administrative and criminal liability in cases of abuse of authority that result in state losses, especially after the issuance of Law Number 30 of 2014 concerning Government Administration. There is an assumption that the return of state losses by the perpetrator can eliminate his criminal liability, even though this is contrary to the provisions of Article 4 of Law Number 31 of 1999 concerning the Eradication of Corruption. This study is a normative legal study with a normative and philosophical juridical approach. The results indicate that the return of state losses does not immediately eliminate criminal liability for corruption. In practice, the results of administrative examinations can be used as evidence in enforcing criminal law. Therefore, coordination between the realm of administrative law and criminal law is important in resolving abuse of authority fairly and effectively.